Beyond the Swell: Decoding the Enigma of Bilateral Hand Angioedema in Response to Sacubitril–valsartan Therapy - Samantha Aster Pinto; Joel Quadros Piedade; Venkatesh Malali; Amar Prabhudesai (Journal of Clinical and Preventive Cardiology)
Angioedema is a rare yet potentially life-threatening side effect associated with renin–angiotensin–aldosterone inhibitors. With angiotensin receptor neprilysin inhibitor replacing angiotensin converting enzyme inhibitors as the preferred treatment for heart failure with reduced ejection fraction, it is crucial for clinicians to recognize the risk of angioedema associated with this therapy. This case report highlights a patient who developed bilateral hand swelling, a week after initiating sacubitril/valsartan. Immediate improvement upon discontinuation of the drug confirms the association with this adverse reaction. Notably, this case presents a unique manifestation of isolated nonpitting hand swelling, previously unreported in the literature, emphasizing the need for heightened physician vigilance and prompt management strategies.